Yield curve in Bosnia and Herzegovina: Financial and macroeconomic framework - Bojan Baskot; Silvije Orsag; Dejan Mikerevic (UTMS Journal of Economics, 2018)
Finance and macroeconomics have different perspectives on the yield curve. In the case of Bosnia and Herzegovina, specific context, data issue and financial market that is in its developing phase, do not allow us to have one, unique perspective. The Nelson-Siegel yield curve model could be appropriate, but additional information provided by factor augmented vectorautoregresion, that is found to be appropriate macro-economic tool, could be crucial for the correct analysis. Nelson-Sigel model performs better than Svensson model in this case, but results interpretation could be confusing. The reason for that could be, the significant importance of 'foreign' factors for the observed economy. Factor analysis allows us to control certain latent factors and in the nexus 'domestic' versus 'foreign' factor this could be crucial feature. The overall relative significance of 'foreign', when it is compared to the significance of the 'domestic' factor, convince us in the importance of exogenous factors for B&H's' economy.
Keywords: 43; E44; G10; 330; Nelson-Siegel model; factor analysis; vector autoregression